TEXTELE DIALECTALE ISTROROMÂNE - O NOUĂ PERSPECTIVĂ DE ABORDARE. - BĂRDĂȘAN, Gabriel; RADU-POP, Ana-Maria (Studii de Ştiintă şi Cultură, 2020)
The aim of our paper is to present a new approach on dialectal Istroromanian texts published until now. The study exposes some ideas which will be the principles of a new editorial project with the title „The Archive of Istroromanian Material and Spiritual Culture. Dialectal Texts and Contexts”. The volume will focus on the content offered by the texts published until now for knowing the ethnic, cultural and linguistic specific. The specific of material and spiritual culture of the Istroromanian linguistic community is somehow reflected in some dialectal texts. The limited access to the content of the Istroromanian transcribed texts, because of the absence (in some published volumes) of an "interdialectal" equivalent or of a translation, justifies the need of a new approach, a new study perspective, in order to enable a wider contact with the Istroromanian speakers' past and present material and spiritual background. Our study exposes the general structure of a future editorial project, the arguments which sustain releasing such a volume, the bibliography on which the texts' thematic split is built and a model of structure and analysis which could be applied to the texts corpora (with specific gastronomic realities as an example). Archiving the particularities of these speakers' material and spiritual "universe" will ensure the knowing of the Istroromanians through the means of elements that regard the essence of their existence.